Biocontrol of Fusarium crown and root rot of tomato and growth-promoting effect of bacteria isolated from recycled substrates of soilless crops - LIU, Jianbin; GILARDI, Giovanna; SANNA, Mattia; GULLINO, Maria; GARIBALDI, Angelo (Phytopathologia Mediterranea, 2010)
Fusarium crown and root rot (FCRR) of tomato caused by Fusarium oxysporum f. sp. radicis-lycopersici is a serious problem in agriculture today. Biological control of this disease may be an effective option to deal with this problem. Antagonistic bacteria isolated from suppressive substrates or soils were tested against FCRR in the glasshouse in a sandy soil mixture infested with the pathogen and compared with other experimental or commercial FCRR biocontrol agents. The antagonistic bacteria were applied twice before artificial infection with the pathogen. Pseudomonas sp. strain FC-24B and P. putida FC-8B provided the best and most effective suppression in all trials, reducing vascular discoloration significantly from 65 to 77% and from 52 to 100% respectively. These strains also reduced root rot by 66% and 70% respectively. Pseudomonas sp. FC-24B also substantially increased plant growth, when the pathogen was absent. Pseudomonas sp. FC-9B, Achromobacter xylosoxydans MM1, Streptomyces griseoviridis strain K61 and the commercial formulation Trichoderma harzianum ICC012 + T. viride ICC080 also gave promising results in terms of disease control.